2012
DOI: 10.1590/s0102-05362012000400032
|View full text |Cite
|
Sign up to set email alerts
|

Incidência de pragas e desempenho produtivo de tomateiro orgânico em monocultivo e policultivo

Abstract: S istemas de produção agrícola com bases agroecológicas vêm ganhando visibilidade nos últimos anos, sendo hoje uma forma de agricultura adequada aos princípios da sustentabilidade e preservação ambiental (Finatto & Côr-rea, 2010), além de ser uma atividade econômica interessante devido à maior valoração de seus produtos e ser uma atividade que oferece segurança ao trabalhador rural. O tomateiro em sistema orgânico destaca-se entre as oleráceas devido ao seu alto valor econômico e ao grande desafio que é seu cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
2
0
6
Order By: Relevance
“…Interestingly, coriander plots had a lower number of leaf beetles as compared with the control plots and the presence of coriander ameliorated the potential ecological risk of attracting a herbivore such as leaf beetles to MeSA‐treated plots. Gomes et al . also reported that coriander intercropped with tomato reduced the abundance of thrips, possibly as a consequence of a repellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, coriander plots had a lower number of leaf beetles as compared with the control plots and the presence of coriander ameliorated the potential ecological risk of attracting a herbivore such as leaf beetles to MeSA‐treated plots. Gomes et al . also reported that coriander intercropped with tomato reduced the abundance of thrips, possibly as a consequence of a repellent effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we arrive at the second axis that focuses on the diversification of the vegetation in polyculture and the use of flower strips through habitat management. This kind of study can be exemplified by works such as [83], who concluded that tomato (Solanum lycopersicum L.) cultivated in polyculture with coriander (Coriandrum sativum L.) (Apiaceae), marigold (Tagetes minuta L.), and sorghum (Sorghum bicolor L.) presented lower losses due to pest attack. On the other hand, [84] stated that the wheat and pea consortium reduces the presence of pests not by increasing the number of natural enemies but by complicating the search of host plant for pests.…”
Section: The Increase Of Parasitoid Action Through Conservative Biolomentioning
confidence: 99%
“…Após este período foi registrado 100% de plantas doentes na lavoura e, portanto, encerradas as avaliações. Conforme proposto por Gomes et al (12) as avaliações foram realizadas por diagnose visual dos sintomas característicos da virose: redução geral do porte da planta, enfezamento, curvamento do ponteiro virado para baixo e lesões necróticas nas hastes. A localização das plantas sadias e doentes em cada avaliação determinou uma malha amostral referente à distribuição da doença no canteiro ao longo do tempo.…”
Section: Grade Amostral E Avaliações Da Doençaunclassified